Modelo matemático del perfil de una leva usando funciones combinadas para simular la fuerza ejercida por el pie al caminar - Valdivieso Alcalde, Pedro Armando (2023)
The purpose of this thesis was to obtain the most optimal cam profile by comparing three design configurations, to simulate the forces exerted by the foot when walking using a cam-follower system. The procedure to follow was the analysis and synthesis for the design of mechanisms. The proposed mechanism consists of a cam-follower system (plunger) that generates pressure to simulate the force exerted when walking. It began by dividing the diagram that establishes the force of the human foot in walking into 5 segments, using the graphic method, the approximate values are found at the characteristic points. The pressures were determined and using the pressure – volume relationship, the displacements in each segment were calculated. Using the Dynacam software, data was entered for the 3 design configurations (cycloidal, modified trapezoidal, and modified sinusoidal) and the characteristics SVAJ graphs were obtained for each one. With the data obtained, the pressure angles and curvature radii were calculated, assuming values for the primary radius, the eccentricity and the radius of the follower roller. It was concluded that the best configuration for the simulation of the force of the foot when walking is the modified sine design because it presents advantages over the other configurations: uniformity in jerk, a lower peak speed and fewer measures in the primitive radius.